Theoretical Study of Second-Order Non-Linear Optical Properties of Two Imino Chromophores Containing Salicylidine Group - SHEIKHSHOAIE, IRAN; SAEID-NIA, SAMIRA; MONADI, NIAZ; KHABAZZADEH, HOJATOLLAH (Asian Journal of Chemistry, 2010)
Two new tridentate imine compounds 4-nitrophenylazo- N-(2-hydroxy propylamine) salicylidine [L1] and phenylazo- N-(2-hydroxy propylamine) salicylidine [L2] have been synthesized and characterized by some spectroscopic techniques. The dipole moment (μ) and the first hyperpolarizabilty (β) and amount of charge density on all coordination atoms, HOMO energy and LUMO energy of L1 and L2 compounds were calculated by using AM1 semi-empirical method. The calculation results reveal this π-conjugated systems have a good nonlinear optical (NLO) property in second harmonic generation technique (SHG). The calculated β (NLO property) for L1 compound is 134.55 times of that urea.